Big Data, exploração ubíqua e propaganda dirigida: novas facetas da indústria cultural - Antunes, Deborah Christina; Maia, Ari Fernando (Instituto de Psicologia da Universidade de São Paulo, 2018)
Abstract The emergence of the so-called digital culture from the development of new information and communication technologies led to criticisms of the concept of cultural industry, elaborated by Horkheimer and Adorno in the 1940s, defining the new configuration based on interactivity, open communication and greater freedom among users. However, to a critical view, the new configuration is even more totalitarian than the previous one. All the actions of users in the digital environment generate information that can be compiled and organized according to mathematical algorithms, configuring the so-called Big Data; such information includes personal preferences, political trends, gender, and even personality profiles, and leads to ubiquitous surveillance and manipulation through targeted advertising, being politically and economically far more effective than in the age of the cultural industry described by Adorno. The update of the critical theory of society implies understanding this new configuration, its pretensions and its contradictions. Therefore, the present article aims both to update the concept of cultural industry denouncing, thus, the new forms of manipulation, and to criticize the idea that freedom is immanent to the Digital Culture, present in its defenders.

Resumen La emergencia de la llamada cultura digital a partir del desarrollo de nuevas tecnologías de información y comunicación llevó a críticas al concepto de industria cultural elaborado por Horkheimer y Adorno en los años cuarenta del siglo pasado, definiendo la nueva configuración a partir de la interactividad, comunicación abierta y mayor libertad entre los usuarios. Sin embargo, a una mirada crítica, la nueva configuración se revela aún más totalitaria que la anterior. Todas las acciones de los usuarios en el entorno digital generan informaciones que pueden ser compiladas y organizadas de acuerdo con algoritmos matemáticos, configurando el llamado Big Data; estas informaciones incluyen datos sobre preferencias personales, tendencias políticas, género e, incluso, perfiles de personalidad, y llevan a intentos de vigilancia ubicua y manipulación por medio de propaganda dirigida, siendo política y económicamente mucho más eficaz que en la era de la industria cultural descrita por Adorno. La actualización de la teoría crítica de la sociedad implica comprender esta nueva configuración, sus pretensiones y sus contradicciones. En este sentido, el presente artículo objetiva tanto actualizar el concepto de industria cultural denunciando así las nuevas formas de manipulación, como criticar la idea de que la libertad es inmanente a la Cultura Digital, presente en sus defensores.

Résumé L’émergence de la culture dite numérique du développement des nouvelles technologies de l’information et de la communication a conduit à critiquer le concept d’industrie culturelle élaboré par Horkheimer et Adorno dans les années 1940, définissant la nouvelle configuration de l’interactivité, de la communication ouverte et plus grande liberté parmi les utilisateurs. Cependant, d’un oeil critique, la nouvelle configuration est encore plus totalitaire que la précédente. Toutes les actions des utilisateurs dans l’environnement numérique génèrent des informations qui peuvent être compilées et organisées selon des algorithmes mathématiques, en configurant les Big Data; ces informations comprennent des données sur les préférences, les tendances politiques, le genre et même les profils de personnalité, et mènent à des tentatives de surveillance et de manipulation omniprésentes par des publicités ciblées, politiquement et économiquement beaucoup plus efficaces qu’à l’ère de l’industrie culturelle décrite par Adorno. L’actualisation de la théorie critique de la société implique de comprendre cette nouvelle configuration, ses prétentions et ses contradictions. En ce sens, le présent article vise à la fois à actualiser le concept d’industrie culturelle dénonçant, ainsi, les nouvelles formes de manipulation, et à critiquer l’idée que la liberté est immanente à la culture numérique, présente chez ses défenseurs.

Resumo A emergência da cultura digital a partir do desenvolvimento de novas tecnologias de informação e comunicação levou a críticas ao conceito de indústria cultural elaborado por Horkheimer e Adorno nos anos 1940, definindo a nova configuração a partir da interatividade, comunicação aberta e maior liberdade entre usuários. Entretanto, a um olhar crítico, a nova configuração se revela mais totalitária que a anterior. Todas as ações dos usuários no ambiente digital geram informações que podem ser compiladas e organizadas de acordo com algoritmos matemáticos, configurando o chamado Big Data; essas informações incluem dados sobre preferências, tendências políticas, gênero e perfis de personalidade, e levam a tentativas de vigilância ubíqua e manipulação por meio de propaganda dirigida, sendo política e economicamente muito mais eficaz do que na era da indústria cultural descrita por Adorno. A atualização da teoria crítica da sociedade implica compreender essa nova configuração, suas pretensões e contradições. Nesse sentido, este artigo objetiva tanto atualizar o conceito de indústria cultural, denunciando, assim, as novas formas de manipulação, quanto criticar a ideia de que a liberdade é imanente à Cultura Digital, presente em seus defensores.
Big Data, ubiquitous exploitation, and targeted advertising: new facets of the cultural industry
Big Data, explotación ubicua y propaganda dirigida: nuevas facetas de la industria cultural
Keywords: cultural industry; critical theory of society; Big Data; digital culture; indústria cultural; teoria crítica da sociedade; Big Data; cultura digital